Tribbles Homolog 3-Mediated Vascular Insulin Resistance Contributes to Hypoxic Pulmonary Hypertension in Intermittent Hypoxia Rat Model - Fan, Fang; He, Jinxiao; Su, Hui; Zhang, Haifeng; Wang, Hao; Dong, Qianqian; Zeng, Minghua; Xing, Wenjuan; Sun, Xin (Frontiers in Physiology, 2020)
This study aimed to investigate the role of vascular insulin resistance (VIR) and Tribbles homolog 3 (TRIB3) in the pathogenesis of hypoxia-induced pulmonary hypertension (HPH). Rats were subjected to low air pressure and low oxygen intermittently for 4 weeks to induce HPH. The mean right ventricular pressure (mRVP), mean pulmonary arterial pressure (mPAP) and right ventricular index (RVI) were significantly increased in HPH rats. Pulmonary arteries from HPH rats showed VIR with reduced vasodilating effect of insulin. The protein levels of peroxisome proliferator-activated receptor gamma (PPARγ), phosphoinositide 3-kinase (PI3K), phosphorylations of Akt and endothelial NO synthase (eNOS) were decreased, and TRIB3 and phosphorylated extracellular signal-regulated protein kinases (ERK1/2) were increased in pulmonary arteries of HPH rats. Early treatment of pioglitazone (PIO) partially reversed the development of HPH, improved insulin-induced vasodilation, and alleviated the imbalance of the insulin signalings. The overexpression of TRIB3 in rat pulmonary arterial endothelial cells (PAECs) reduced the levels of PPARγ, PI3K, p-Akt, and p-eNOS, increased p-ERK1/2 and the synthesis of ET-1, which were further intensified under hypoxic conditions. Moreover, TRIB3 knockdown caused significant improvement in Akt and eNOS phosphorylations and otherwise a reduction of ERK1/2 activation in PAECs after hypoxia. In conclusion, impaired insulin-induced pulmonary vasodilation and the imbalance of insulin-induced signalings mediated by TRIB3 upregulation in the endothelium contribute to the development of HPH. Early PIO treatment improves vascular insulin sensitivity that may help to limit the progression of hypoxic pulmonary hypertension.